First detection of Hyalomma rufipes in Germany - Chitimia-Dobler, Lidia; Nava, Santiago; Bestehorn, Malena; Dobler, Gerhard; Wölfel, Silke (2018)
Hyalomma rufipes, a two-host tick, is the most widespread Hyalomma species in Africa. In December 2015, an ixodid tick male with an unusual morphology was detected on a horse in a stable near Mainz in the Federal State Rhineland-Palatine. For identification purposes, the tick was preserved in alcohol and sent to our laboratory. The morphology of the tick showed specific characteristics of H. rufipes. The 16S rDNA sequence of H. rufipes from Germany was identical to the corresponding 16S rDNA sequence of H. rufipes from Tanzania, and they both were closely related to Hyalomma marginatum. The tick was tested with a real-time PCR for rickettsiae and Crimean-Congo hemorrhagic fever (CCHF) virus with negative results.